How different do visuo‐tactile criteria assess caries lesions activity status on occlusal surfaces?. (14th August 2014) - Floriano, I; Bonini, GC; Matos, R; Novaes, TF; Ekstrand, KR; Mendes, FM; Braga, MM
Abstract : Objectives: We tested the association between active caries lesions assessed by two different criteria and clinical features of these caries lesions. Materials and methods: Three examiners examined forty‐nine 3‐ to 12‐year‐old children: one examiner used the Nyvad criteria, another examiner used the International Caries Detection and Assessment System with an additional criteria – Lesion Activity Assessment (ICDAS + LAA), and a reference examiner classified lesions regarding plaque stagnation, colour, lustre, cavities, depth and texture. Logistic regressions were used to test associations. For analyses, we grouped sound sites and inactive lesions vs active caries lesions, but also considering only inactive vs active lesions. Results: Active lesions scored by both criteria were similarly associated with different clinical parameters tested, except when the sound sites were excluded from the analysis. In these cases, active lesions according to ICDAS + LAA were associated only with cavitation and texture. Texture was associated with divergences between criteria when differentiating sound or inactive lesions from active ones. Fewer divergences in differentiating active from inactive lesions were observed when lesions present lustre. Conclusion: Most clinical signs associated with active caries lesions were similar, but texture and severity tend to have a greater importance when using ICDAS + LAA for distinguishing caries activity status. Attention should be given to differences due to texture and lustre when using different indices.